BEHAVIORAL–TECHNOLOGY MODEL DALAM ADOPSI DIGITAL PAYMENT: DAMPAKNYA TERHADAP EFISIENSI KEUANGAN UMKM DI OEBOBO, KOTA KUPANG - Irmina Linda Dewiaty; Andrias Umbu Tuku Anabuni (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the effect of digital payment adoption on the financial efficiency of UMKM in Oebobo District, Kupang City.Methods: This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) as the analytical technique. The research sample consists of 107 UMKM owners who have adopted digital payment systems, including QRIS, e-wallets, and mobile banking. The sampling technique used is purposive sampling.Results: The findings indicate that trust in digital technology and perceived ease of use have a significant positive effect on digital payment adoption. In contrast, financial literacy and infrastructure/regulatory support do not have a significant effect. Digital payment adoption is proven to enhance the financial efficiency of UMKM, particularly in terms of cash flow efficiency and financial transparency.Conclusion: These findings reinforce the Technology Acceptance Model (TAM) and the Behavioral Finance approach, emphasizing that trust and perceived ease of use significantly influence digital payment adoption among UMKM in Oebobo District. The adoption of digital payment systems is empirically proven to improve UMKM financial efficiency. Keywords: Behavioral Finance, Digital Payment, Financial Efficiency, MSMEs, TAM